Nuestra Recuperación [Our Recovery]: using photovoice to understand the factors that influence recovery in Latinx populations - Jordana Muroff; Daniel Do; Cristina Araujo Brinkerhoff; Deborah Chassler; Myrna Alfaro Cortes; Michelle Baum; Genessis Guzman-Betancourt; Daniela Reyes; Luz M. López; Maylid Roberts; Diliana De Jesus; Emily Stewart; et al. (BMC, 2023)
Abstract Background Photovoice is a form of visual ethnography intended to engage impacted communities in research followed by action to ameliorate the injustices under study. Photovoice has increased in use, especially in collaboration with Latinx communities addressing health inequities. The Latinx population comprises nearly 18% of the overall United States population and according to the census is projected to reach just under 30% by 2060. This diverse panethnic community faces significant structural barriers in accessing services. Racism and the resulting marginalization, specifically, contributes to limited access to recovery services and treatment. Making meaningful advances in substance use disorder training, intervention and policy necessitates learning alongside the Latinx community. Methods We partnered with a Latinx serving integrated behavioral health and primary care setting in Boston Massachusetts to explore barriers and facilitators to recovery using photovoice. Spanish-speaking Latinx adults with a substance use disorder participated. The group met for three photovoice sessions over a six-week period. Together group members critically analyzed photographs using the SHOWeD method. Results Findings indicate a sense of purpose and meaning, security, faith and housing are important elements of recovery. The results illustrated the importance of sources of connection in maintaining sobriety. Through this photovoice project, Latinx Spanish speaking participants highlighted barriers and facilitators to their substance use disorder recovery which spanned individual, community, and structural levels. Conclusions The experiences and voices of the Latinx community are crucial to drive discussions that advance policy (e.g., housing stability and access), enhance providers' understanding of Latinx Spanish-speakers' substance use disorder recovery, and inform culturally and linguistically appropriate services. This study demonstrated that photovoice is highly acceptable and feasible among Latinx clients receiving substance use disorder services. Visual images related to housing, faith, etc. communicate challenges, power structures, as well as hopes to policymakers at multiple levels (e.g., institution/ agency, state).